2012
DOI: 10.1111/jai.12106
|View full text |Cite
|
Sign up to set email alerts
|

Weight-length relationships of 14 species of icefishes (Salangidae) endemic to East Asia

Abstract: Summary Length‐weight relationships (LWRs) of 14 species from 17 populations of salangids, which cover most species in the family Salangidae, were analyzed from 12 regions in China and Japan. A total of 952 specimens were used to estimate the relationship parameters. The allometric factor b values varied from 2.56 in Salanx cuvieri to 3.53 in Neosalanx oligodontis. Additionally, the condition factor a value was calculated setting b = 3 in the remaining six species. Nine maximum‐size records and 17 LWRs of sala… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
5
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 9 publications
0
5
0
Order By: Relevance
“…Freshwater icefish occur in the lentic bays, gulfs and estuaries of open lakes and reservoirs, and marine species are distributed in estuarine and coastal areas (Zhang et al 2007a). China has the largest population of icefish worldwide, with the natural distribution ranging from Bohai Sea to Beibu Gulf and river systems such as Heilongjiang River, Yalu River, Liaohe River, Haihe River, Qiantang River, Pearl River and Yangtze River (Zhang et al 2012). Affiliated lakes of the Yangtze River, including Poyang Lake, Dongting Lake, Taihu Lake, Hongze Lake and Chaohu Lake (the five biggest freshwater lakes in China in sequence), are the main icefish-producing areas .…”
Section: Introductionmentioning
confidence: 99%
“…Freshwater icefish occur in the lentic bays, gulfs and estuaries of open lakes and reservoirs, and marine species are distributed in estuarine and coastal areas (Zhang et al 2007a). China has the largest population of icefish worldwide, with the natural distribution ranging from Bohai Sea to Beibu Gulf and river systems such as Heilongjiang River, Yalu River, Liaohe River, Haihe River, Qiantang River, Pearl River and Yangtze River (Zhang et al 2012). Affiliated lakes of the Yangtze River, including Poyang Lake, Dongting Lake, Taihu Lake, Hongze Lake and Chaohu Lake (the five biggest freshwater lakes in China in sequence), are the main icefish-producing areas .…”
Section: Introductionmentioning
confidence: 99%
“…What is more, The LWR parameters a and b of the fish are readily affected by a series of factors such as season, habitat, gonad maturity, sex, diet and stomach fullness, health, preservation methods, and annual differences in environmental conditions (Froese 2006). The length-weight relation of some species have been studied in China and other localities (Yie 1988, 1993, Chen et al 1989, Wang et al 1996, Xu et al 1996, Xiao et al 2002, Yalçın et al 2002, Kimmerer et al 2005, Ye et al 2007, Garcia 2010, Ujjania et al 2012, Zhang et al 2013, and a and b values as well as r 2 values reported in these studies are presented in Table 2 for a comparison. Dissimilarities seen between present study and results given by various researchers may be attributed the fishing methodology and physical conditions of the habitat (water depth and temperature, sandy and vegetated bottom structures and oxygen).…”
mentioning
confidence: 99%
“…N. taihuensis is endemic to fresh and brackish waters widely distributed in China and has been artificially introduced to numerous lakes and reservoirs due to its high commercial value 4 . The natural population is not only distributed in the estuary area from the Yellow and Bohai Seas to the coast of the South China Sea but also in the main streams of the Yangtze River, Huai River and Yellow River and their subsidiary lakes 5 , 6 . Among these sites, the Yangtze River basin and Taihu Lake are the core habitats of the natural population of N. taihuensis 7 9 .…”
Section: Background and Summarymentioning
confidence: 99%